2016
DOI: 10.1007/s10565-016-9343-z
|View full text |Cite
|
Sign up to set email alerts
|

Variations of chromosome 2 gene expressions among patients with lung cancer or non-cancer

Abstract: Lung cancer is one of the most common malignancies worldwide. The present study aimed to investigate specific genotypes of different subtypes or stages of lung cancer through gene expression variations of chromosome 2 genes, trying to identify predictors for diagnosis or prognosis of lung cancer. About 537 patients with lung adenocarcinoma (ADC), 140 patients with lung squamous carcinoma (SQC), 9 patients with lung large cell carcinoma (LCC), 56 patients with small cell lung cancer (SCLC), and 590 patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(29 citation statements)
references
References 47 publications
1
28
0
Order By: Relevance
“…Several studies have linked CORVET, CHEVI and HOPS subunits to cancer progression. High levels of Vps3 correlate with poor prognosis of human squamous carcinoma lung cancer (Bao et al, 2016). Single nucleotide polymorphisms in Vps41 strongly associate with hereditary melanoma (Ibarrola-Villava et al, 2015), and a recent study reported Vps33B as an important tumor suppressor in hepatocarcinogenesis (Wang et al, 2018).…”
Section: Cancermentioning
confidence: 99%
“…Several studies have linked CORVET, CHEVI and HOPS subunits to cancer progression. High levels of Vps3 correlate with poor prognosis of human squamous carcinoma lung cancer (Bao et al, 2016). Single nucleotide polymorphisms in Vps41 strongly associate with hereditary melanoma (Ibarrola-Villava et al, 2015), and a recent study reported Vps33B as an important tumor suppressor in hepatocarcinogenesis (Wang et al, 2018).…”
Section: Cancermentioning
confidence: 99%
“…Genome-wide association studies on lung cancer, lung function, and COPD have identified a number of overlapping Bsusceptibility^loci. With stringent phenotyping, several overlapping loci are independently associated with both COPD and lung cancer, but with pulmonary inflammation and apoptotic processes mediated by the bronchial epithelium (Bondarczuk and PiotrowskaSeget 2013;Corbel et al 2002;Bao et al 2016a). Some lung cancer-specific genetic variants were identified as BCOPD-related^genetic variants associated with clinical variables (Young et al 2011).…”
mentioning
confidence: 99%
“…For example, the expression of CCL20 in lung cancer cells is higher in patients with advanced lung cancer than in patients with early-stage lung cancer, and this high expression is associated with a poor prognosis. Bao et al reported that the CCL20 gene may be a prognostic risk factor or protective factor for lung adenocarcinoma [28]. These observations mean that the unstable expression of these genes can cause different oncological outcomes.…”
Section: Discussionmentioning
confidence: 99%